1988
DOI: 10.1111/j.1559-1816.1988.tb01198.x
|View full text |Cite
|
Sign up to set email alerts
|

Subject Competence and Minimization of the Bystander Effect

Abstract: While performing a drawing task, either alone or in the presence of an observer, high‐ and low‐competent subjects heard a workman fall off a ladder in an adjoining room. As expected, high‐competent subjects (Registered Nurses) who witnessed the emergency with another bystander helped as frequently as subjects who witnessed the emergency alone; low‐competent subjects (general students) evidenced the familiar bystander effect. Responses to the post‐emergency questionnaire indicated that at the time of the emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 33 publications
2
51
0
2
Order By: Relevance
“…Moral frames such as tribe caring and social-hierarchy-dependent morality influenced how schoolchildren behaved in bystander situations. In addition, social psychological aspects such as social categorization, in-group and out-group membership (i.e., being or not being a tribe member), and social roles that indicate status, leadership (compare with Baumeister et al, 1988), or competence (compare with Cramer et al, 1988) played an important role. Even if well-known social psychological processes behind bystander effects, such as pluralistic ignorance (Bierhoff, 2002;Darley et al, 1973;Latané & Darley, 1970), audience inhibition (Bierhoff, 2002;Hogg & Vaughan, 2008), and diffusion of responsibility (Latané & Darley, 1970), are possible heuristic concepts, the current study's context sensitivity, based on an ethnographic and GT approach, shows the importance of challenging as well as further developing and integrating these extant concepts with newer concepts in order to more fully explain the bystander behavior among students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moral frames such as tribe caring and social-hierarchy-dependent morality influenced how schoolchildren behaved in bystander situations. In addition, social psychological aspects such as social categorization, in-group and out-group membership (i.e., being or not being a tribe member), and social roles that indicate status, leadership (compare with Baumeister et al, 1988), or competence (compare with Cramer et al, 1988) played an important role. Even if well-known social psychological processes behind bystander effects, such as pluralistic ignorance (Bierhoff, 2002;Darley et al, 1973;Latané & Darley, 1970), audience inhibition (Bierhoff, 2002;Hogg & Vaughan, 2008), and diffusion of responsibility (Latané & Darley, 1970), are possible heuristic concepts, the current study's context sensitivity, based on an ethnographic and GT approach, shows the importance of challenging as well as further developing and integrating these extant concepts with newer concepts in order to more fully explain the bystander behavior among students.…”
Section: Discussionmentioning
confidence: 99%
“…Certain social norms, such as the social responsibility norm (Rutkowski, Gruder, & Romer, 1983) or the altruistic norm (Horowitz, 1971), among bystanders seem to counteract or reduce the bystander effect and instead increase the likelihood of helping behavior. Social roles that indicate subject competence, such as being a nurse or a doctor (Cramer, McMaster, Bartell, & Dragna, 1988), or a generalized responsibility, such as leadership roles (Baumeister, Chesner, Senders, & Tice, 1988), may also increase the likelihood of helping behavior.…”
Section: Bystander Effectmentioning
confidence: 99%
“…Some have shown that prospective training ("induced competence") as an experimental variable significantly reduced psychosocial barriers to exhibiting "helping behavior" (in this case, providing first aid) in a mock emergency, whether subjects were acting alone or in a group. [37][38][39] These studies were relatively short term, separating subject training and subsequent exposure to a mock emergency by only 3 to 9 weeks, depending on the study.…”
Section: Long-term Impact: Training For the Futurementioning
confidence: 99%
“…Cramer, McMaster, Bartell & Dragna, 1988;Pantin & Carver, 1982;Tice & Baumeister, 1985), to the author's knowledge there has been no investigation of this phenomenon in computer-mediated communications (e.g. chat rooms, news groups).…”
Section: Introductionmentioning
confidence: 99%